Establishing parasegments in Drosophila embryos: roles of the odd-skipped and naked genes. - Mullen, J.R.; DiNardo, S. (Developmental Biology, 1995)
During Drosophila embryogenesis, a genetic cascade establishes repeating developmental units, the parasegments, along the anterior-posterior axis. Anterior and posterior boundaries of parasegments are defined by narrow stripes of cells expressing the segment polarity genes engrailed and wingless, respectively. Through single and double mutant analysis, we describe genetic interactions regulating the precise activation of engrailed and wingless in alternate parasegments. The pair-rule gene odd-skipped and the segment polarity gene naked are both required to restrict engrailed expression. odd-skipped represses expression of fushi tarazu, a known activator of engrailed. naked prevents activation of engrailed by fushi tarazu, without affecting fushi tarazu expression. engrailed expression is thus limited to narrow stripes of cells at the anterior boundaries of these parasegments. wingless expression is regulated by both odd-skipped and the pair-rule gene paired. odd-skipped represses wingless expression, while paired restricts the domain of expression of odd-skipped. wingless expression is thus allowed in narrow stripes of cells at the posterior boundaries of these parasegments. Accurate expression of engrailed and wingless is also required for cells within each parasegment to assume their proper positional identity. In odd-skipped mutants, the positional identities of particular cells are changed, creating mirror-image duplications of the body pattern. We present a model describing how the altered expression patterns of fushi tarazu, engrailed, and wingless generate the mutant phenotype.